2021
DOI: 10.2147/jhl.s288682
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Joint Commission International Accreditation in Improving Quality at King Fahd University Hospital, Saudi Arabia: A Mixed Methods Approach

Abstract: Introduction Saudi Arabia has one of the highest numbers of health organizations accredited by the Joint Commission International. This study aimed to measure this process’s effectiveness in improving quality at King Fahd Hospital of the University in Khobar, Saudi Arabia. Additionally, the study investigated health providers’ perceptions of this process. Materials and Methods This research utilized a convergent parallel mixed method. For the quantitative analysis, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
(47 reference statements)
0
10
0
1
Order By: Relevance
“…19 Study in a University Hospital, Saudi Arabia shows the percentage of laboratory critical value reporting within 30 minutes had high compliance (99,37%) as they already stick to the College of American Pathologists (CAP) Laboratory Accreditation Program. 20 It seems accreditation and the sequence like training could bring a good impact to the timeliness of laboratory critical value reporting.…”
Section: Resultsmentioning
confidence: 99%
“…19 Study in a University Hospital, Saudi Arabia shows the percentage of laboratory critical value reporting within 30 minutes had high compliance (99,37%) as they already stick to the College of American Pathologists (CAP) Laboratory Accreditation Program. 20 It seems accreditation and the sequence like training could bring a good impact to the timeliness of laboratory critical value reporting.…”
Section: Resultsmentioning
confidence: 99%
“…It was certainly perceived positively that accreditation improved different aspects of patient care, and believed that several issues need to be considered in future accreditation cycles. 1,[20][21][22] In addition, a descriptive-analytical study illustrated that the accreditation status is boosted due to the health care professional's understanding of accreditation standards and belief in its impact on early identification of performance gaps, especially in the essential safety requirements. 23 In our previous research study done by the accreditation division in JHAH, we used quality performance indicators to measure the impact of accreditation, where the compliance with JCI standards was measured by the performance of the 6 IPSGs, which was directly reflected in improving quality and patient safety over time.…”
Section: Discussionmentioning
confidence: 99%
“…National studies indicated that the JCIA positively impacted the participation, preparation, and quality of health care provided at the hospital, though the degree of impact contrasted among various health professionals. It was certainly perceived positively that accreditation improved different aspects of patient care, and believed that several issues need to be considered in future accreditation cycles 1,20–22. In addition, a descriptive-analytical study illustrated that the accreditation status is boosted due to the health care professional's understanding of accreditation standards and belief in its impact on early identification of performance gaps, especially in the essential safety requirements 23.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of JCI accreditation on the quality of care and performance have been assessed in different countries since 2010. In one study, the author concluded that pursuing JCI accreditation positively impacted 75% (9/12) of a select list of clinical measures at the 550-bed King Fahd Hospital in Saudi Arabia [10]. In another study, 60% (3/5) of the studied performance indicators achieved signi cant improvements due to JCI accreditation; this was found by comparing two 133-bed accredited hospitals and two 115-bed unaccredited hospitals in Jordan [11].…”
Section: Literature Review On the Impact Of Hospital Accreditationmentioning
confidence: 99%